Cell Culture Based in vitro Test Systems for Anticancer Drug Screening - Kitaeva, Kristina V.; Rutland, Catrin S.; Rizvanov, Albert A.; Solovyeva, Valeriya V. (Frontiers in Bioengineering and Biotechnology, 2020)
The development of new high-tech systems for screening anticancer drugs is one of the main problems of preclinical screening. Poor correlation between preclinical in vitro and in vivo data with clinical trials remains a major concern. The choice of the correct tumor model at the stage of in vitro testing provides reduction in both financial and time costs during later stages due to the timely screening of ineffective agents. In view of the growing incidence of oncology, increasing the pace of the creation, development and testing of new antitumor agents, the improvement and expansion of new high-tech systems for preclinical in vitro screening, is becoming very important. The pharmaceutical industry presently relies on several widely used in vitro models, including two-dimensional models, three-dimensional models, microfluidic systems, Boyden's chamber and models created using 3D bioprinting. This review outlines and describes these tumor models including their use in research, in addition to their characteristics. This review therefore gives an insight into in vitro based testing which is of interest to researchers and clinicians from differing fields including pharmacy, preclinical studies and cell biology.